Automated Water Quality Monitoring IOT System for Small-scale Aquaculture Farms - Menon, Aishwarya Girish; M, Prabhakar (International Journal of Computer Sciences and Engineering, 2020)
The traditional way of monitoring water quality of aquaculture ponds like fish farms and shrimp farms is to do it every few hours so as to minimize the stress to the animal and to minimize the mortality rate. The entire process is a tedious task involving manpower for collection of water samples and performing several lab tests. This results in unnecessary requirement of man power and in efficient usage of time thereby affecting the farmer’s economic returns and ultimate sustenance. This proposed IoT System uses Arduino development board with sensors for cost effectiveness and provides a real time monitoring environment whereby data is collected from certain specified areas of the pond every few hours and sent as an SMS via the GSM module to the farmer’s mobile along with a warning in case any of the parameters have crossed the defined range. The System will be powered by Solar Panels so that the device need not be charged manually thus automating the system.